2001
DOI: 10.3177/jnsv.47.201
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Toxicity of Fish Oil Concentrates in Male and Female Rats.

Abstract: SummaryThere are an overwhelming number of reports indicating the beneficial effects of fish oil supplements in human and animal nutrition. The purpose of this study, second in a series, was to evaluate the effects, particularly those that may be harmful, of high-dose, long-term consumption of fish oil concentrates (FOC) using male and female rats. One hun dred and twenty male and 120 female rats were gavaged daily with oils and oil mixtures in a volume equal to 0.5% body weight (5mL/kg/d) for 13 weeks. The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…This was not observed in the present study, and no differences were detected in average weight gain between the two dietary groups during preoperative or postoperative periods. The triglyceride levels were reduced but not so significantly in the fish oil-fed group, in agreement with the results reported by Rabbani et al (2001). Cholesterol levels presented no differences among groups, in contrast to the data reported by Rabbani et al (2001), who observed reduced cholesterol levels in rats treated with high doses of fish oil (5 ml of fish oil/kg/day).…”
Section: Discussionsupporting
confidence: 91%
“…This was not observed in the present study, and no differences were detected in average weight gain between the two dietary groups during preoperative or postoperative periods. The triglyceride levels were reduced but not so significantly in the fish oil-fed group, in agreement with the results reported by Rabbani et al (2001). Cholesterol levels presented no differences among groups, in contrast to the data reported by Rabbani et al (2001), who observed reduced cholesterol levels in rats treated with high doses of fish oil (5 ml of fish oil/kg/day).…”
Section: Discussionsupporting
confidence: 91%
“…Whether this was due to reduced resorption of dietary calories in the HF-F rats or to elevation of energy expenditure cannot be decided from our data, but previous studies point to enhanced thermogenesis in fish oil-fed rats through increasing the expression of mitochondrial uncoupling proteins and increasing fatty acid oxidation by the less efficient peroxisomal pathway (Oudart et al 1997, Baillie et al 1999. Hepatomegaly induced by fish oil-feeding has been described consistently before (Otto et al 1991, Yaqoob et al 1995, Rabbani et al 2001, Nakatani et al 2003, but the extent of hepatic fat deposition in fish oil-fed rats remains controversial. Some studies report an elevated (Otto et al 1991, Yaqoob et al 1995 and others a lowered liver lipid content (Levy et al 2004), a finding that might reflect either differences induced by the specific dietary source or rat strain-dependent variability.…”
Section: Discussionmentioning
confidence: 46%
“…Some studies in rats (11,12) and humans (13)(14)(15) have suggested that fish oil FA may decrease CVD risk in part by decreasing osmolar fragility and increasing the deformability of red blood cells. In the present study, we tested for the first time the impact on red cell fragility of fish oil FA in the form of plant sterol esters.…”
Section: Figmentioning
confidence: 99%
“…Whether the detrimental effects of plant sterols on spontaneously hypertensive rats can be extrapolated to healthy animals and other animal species still remains to be determined. On the other hand, fish oil FA, via their incorporation in red blood cell membrane phospholipids, may improve erythrocyte lipid fluidity and deformability, and consequently reduce their fragility (11)(12)(13)(14)(15). It can be hypothesized that the esterification of plant sterols to fish oil FA may protect red blood cells against the increased fragility potentially associated with plant sterol consumption.…”
mentioning
confidence: 99%